Intermolecular channels direct crystal orientation in mineralized collagen - Xu, YiFei; Nudelman, Fabio; Eren, E. Deniz; Wirix, Maarten J. M.; Cantaert, Bram; Nijhuis, Wouter H.; Hermida-Merino, Daniel; Portale, Giuseppe; Bomans, Paul H. H.; Ottmann, Christian; Friedrich, Heiner; Bras, Wim; et al. (Nature communications, 2020)
The mineralized collagen fibril is the basic building block of bone, and is commonly pictured as a parallel array of ultrathin carbonated hydroxyapatite (HAp) platelets distributed throughout the collagen. This orientation is often attributed to an epitaxial relationship between the HAp and collagen molecules inside 2D voids within the fibril. Although recent studies have questioned this model, the structural relationship between the collagen matrix and HAp, and the mechanisms by which collagen directs mineralization remain unclear. Here, we use XRD to reveal that the voids in the collagen are in fact cylindrical pores with diameters of ~2 nm, while electron microscopy shows that the HAp crystals in bone are only uniaxially oriented with respect to the collagen. From in vitro mineralization studies with HAp, CaCO 3 and γ-FeOOH we conclude that confinement within these pores, together with the anisotropic growth of HAp, dictates the orientation of HAp crystals within the collagen fibril. Mineralized collagen is the building block of bone but how the collagen directs hydroxyapatite formation remains unclear. Here, the authors demonstrate cylindrical pores in collagen and how the anisotropic growth of hydroxyapatite directs the orientation of crystal growth in mineralized collagen.